Iron homeostasis in mice: does liver lobe matter? - Colucci, Silvia; Carvalho Oliveira, Tiago; Muckenthaler, Martina; Marques, Oriana (American journal of physiology. Gastrointestinal and liver physiology, 2023)
The liver plays a crucial role in maintaining systemic iron homeostasis through iron storage, sensing of systemic iron needs, andproduction of the iron-regulatory hormone hepcidin. While mice are commonly used as models for studying human iron homeo-stasis, their liver structure differs significantly from humans. Since the mouse liver is structured in six separated lobes, often, theanalysis of a single defined lobe is preferred due to concerns over data reproducibility between experimental cohorts. In thisstudy, we compared iron-related parameters in distinct liver lobes of C57BL/6 wild-type mice across different ages. We foundthat the non-heme iron levels, as well as the mRNA and protein expression of iron storage protein Ferritin and the iron importerTransferrin Receptor 1, were similar between liver lobes. Additionally, the mRNA expression ofHepcidin, as well as its regulators,Bmp2andBmp6, and iron importersZip8andZip14were comparable. Minor differences were observed inFerroportinmRNAlevels of 24-wk-old mice; however, this did not correlate with altered iron content. Thefindings in wild-type mice were repro-duced inHfeknock-out mice–a well-established genetic model of the most prevalent form of hemochromatosis. Overall, ourresults indicate that C57BL/6 mouse liver lobes can be used interchangeably for assessing iron content and expression ofiron-related genes. Understanding if thesefindings are applicable to other mouse developmental stages, strains, or models of(iron-related) disorders will be key to promote reduction of experimental animal numbers and facilitate resource sharingamong research groups studying liver iron homeostasis.
Online veröffentlicht: 5. September 2023
Gesehen am 02.04.2024